The impact of COVID-19 lockdown on internet use and escapism in adolescents - Fernandes, B; Biswas, UN; Tan-Mansukhani, R; Vallejo, A; Essau, CA (Revista de Psicologia Clinica con Ninos y Adolescentes, 2020)
The COVID-19 pandemic has had a significant impact on everyday functioning, considerable measures being taken to reduce the spread of the virus. Schools and social avenues have been placed on prolonged lockdowns, with people continuing to maintain physical distance. Adolescents and young people have had to endure significant stress alongside dealing with developmental characteristics. Amidst all of this, studies report an increase in gaming addiction and internet use with detrimental impact on psychosocial well-being. The aim of the present study was to examine the impact of lockdown on internet use in adolescents, comparing their habits from before the pandemic. Furthermore, this research aimed to investigate the relationship between gaming addiction, internet use and COVID-19 worries. Adolescents from several countries (e.g., India, Malaysia, Mexico and the UK) completed online questionnaires, shared via social media and youth networks. These measures included questions on internet, social media, gaming, depression, loneliness, escapism and COVID-19. Results show that adolescents generally have increased their use of social media sites and streaming services. Further, those who scored highly on gaming addiction, compulsive internet use and social media use also reported high scores of depression, loneliness, escapism, poor sleep quality and anxiety related to the pandemic. Our findings indicate that, regardless of country of residence, the COVID-19 outbreak has had a significant effect on adolescent internet use and psychosocial well-being. The need to address pandemic related distress to reduce the effect of maladaptive coping strategies is highlighted.